UPAYA MENGOPTIMALKAN AKTIVITAS BELAJAR KONSEP MONOHIBRID UNTUK BERLATIH BERPIKIR KRITIS MELALUI STRATEGI REACT - KARTIKASARI, DARWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
Efforts to think carefully in the learning process will provide students with critical thinking skills, namely: becoming strong problem solvers, mature decision makers, and will be more focused in analyzing the knowledge they already have. In this research, researchers used the REACT learning strategy as an effort to optimize learning activities to train critical thinking skills. A student has gone through an active learning process if he is able to demonstrate critical thinking skills, understand a problem, connect one information with other information, so that various perspectives emerge, and find a solution to a problem. In this research, the REACT strategy can optimize learning activities through cycle 1 with an achievement of 66.73% and an increase in learning activities in cycle 2 of 77.12%. The REACT strategy is also able to develop students' character to socialize in carrying out learning activities. With the development of fairly good social attitudes (74.62%), it also influences cognitive abilities with an achievement of 77%. Efforts to optimize learning activities accompanied by developing the affective domain resulted in competency test achievement of 81.52%. Thus, through the REACT strategy, learning activities can be increased which are able to build students' critical thinking skills to analyze